Effect of Composition on Polarization Hysteresis and Energy Storage Ability of P(VDF-TrFE-CFE) Relaxor Terpolymers - Hambal, Yusra (Polymers (Basel), 2021)
The temperature dependence of the dielectric permittivity and polarization hysteresis loops of P(VDF-TrFE-CFE) polymer films with different compositions are studied. Among them, the three compositions, 51.3/48.7/6.2, 59.8/40.2/7.3, and 70/30/8.1, are characterized for the first time. Relaxor behavior is confirmed for all studied samples. Increasing the CFE content results in lowering the freezing temperature and stabilizes the ergodic relaxor state. The observed double hysteresis loops are related to the field-induced transition to a ferroelectric state. The critical field corresponding to this transition varies with the composition and temperature; it becomes larger for temperatures far from the freezing temperature. The energy storage performance is evaluated from the analysis of unipolar polarization hysteresis loops. P(VDF-TrFE-CFE) 59.8/40.2/7.3 shows the largest energy density of about 5 J·cm(−3) (at the field of 200 MV·m(−1)) and a charge–discharge efficiency of 63%, which iscomparable with the best literature data for the neat terpolymers.